Greater bed- and wake-time variability is associated with less healthy lifestyle behaviors: a cross-sectional study - Duncan, M.; Kline, C.; Rebar, Amanda; Vandelanotte, C.; Short, C. (Springer, 2016)
© 2015, Springer-Verlag Berlin Heidelberg. Aim: This study examines associations between the variability in bed/rise times, usual bed/rise time and dietary quality, physical activity, alcohol consumption, sitting time, sleep insufficiency and a composite index of behaviors. Subject and methods: A random sample of Australian adults drawn from an online Panel cohort in 2013 completed a cross-sectional online survey. A total of 1,317 participants, median age 57 (IQR = 20) completed the survey. Bed- and wake times, variability in bed- and wake-times, dietary quality, physical activity, alcohol consumption, sitting time, sleep insufficiency and socio-demographics were assessed using a questionnaire. Associations were examined with generalized linear models. Results: Having bed - times that varied by >30 min were associated with lower dietary quality, higher alcohol consumption, higher sitting time, more frequent insufficient sleep and poorer overall pattern of lifestyle behaviors. Greater variability in wake times, usual bed times and usual wake times were inconsistently associated with lifestyle behaviours. Conclusions: Greater bed-time variability is associated with a less healthy pattern of lifestyle behaviors. Greater consistency in sleep timing may contribute to, or be reflective of, a healthier lifestyle.